Implementation of Eco-Humanism in Resolving Tourism Disputes in Sigedang Village, Based on Restorative Justice - Wijayanti, Asri; Ekasari, Ratna; Zamroni, M.; Prasetyo, Rudy Wahyu; Abdillah, Hanif; Cahyarini, Nindy Septian (Journal of Ecohumanism, 2024)
This study finalizes the settlement of tourism disputes in tourism villages based on eco-humanism. The purpose of this study is to find out and analyse the results of exploration of tourism dispute resolution in villages/tourist destinations based on eco-humanism. By using qualitative research methods through primary and secondary data sources, this study examines the contribution to the application of eco-humanism as the basis for sustainable ecotourism development, in resolving tourism disputes in Sigedang Village based on restorative justice. The results of the study show that tourism disputes in the civil field (management of tourist attractions) and in the criminal field (adultery and extortion) are resolved in a non-litigation manner, by applying eco-humanism, based on restorative justice. The recommendations given require an active role in synergy between stakeholders (Village Apparatus, Village/Tourist Spot managers, Communities, Regional Governments and academics) in realizing the making of legal rules that reflect eco-humanism in Tourism Villages.